Could fasciotomy prevent amputation in patients with electrical burn injuries? Insights from a cross-sectional study in Indonesia - Hidayati, Citra A.; Saputro, Iswinarno D.; Hutagalung, Magda R. (Narra J, 2024)
The amputation rate resulting from electrical burn injuries remains high, yet no study has investigated whether early fasciotomy may reduce the amputation rate. The aim of this study was to analyze the success rate of fasciotomy in preventing amputation and determine the optimal timing for fasciotomy in electrical burn injuries. This study was conducted at Dr. Soetomo Hospital from January 2020 to July 2023. Total sampling was employed to recruit the patients. Clinical data, voltage characteristics, burn location, affected total body surface area, burn depth, hospital arrival time, and time interval from incident to fasciotomy were assessed. Chi-squared test was used to assess factors associated with the fasciotomy incidence and factors associated with amputation after fasciotomy. A total of 45 patients were included of which 97.8% were male with a mean age of 37.60-year-old. Approximately 73% of patients had full-thickness burn injuries, with the left upper extremity being the most affected (80%). There are seven patients (15.6%) had fasciotomy and five (11.1%) patients had an amputation. Our data indicated a significant association between voltage characteristics and fasciotomy incidence (p=0.034). Additionally, our data indicated that earlier arrival to the hospital (p=0.002) and timely fasciotomy conducted upon arrival (p<0.001) were associated with a reduced rate of amputation. This study highlights that prompt arrival to the hospital and early fasciotomy may prevent amputation in patients with electrical burn injuries.